2021
DOI: 10.1097/md.0000000000026648
|View full text |Cite
|
Sign up to set email alerts
|

A seven-m6A regulator-related CpG site-based prognostic signature for endometrial carcinoma

Abstract: Background Endometrial carcinoma (EC) has become a common gynecologic malignancy with a high mortality. The m 6 A regulators have been identified to be closely associated with multiple human cancers including EC. However, the CpG methylation signature related to m 6 A regulators in EC remains unclear.Method The methylation profiles of EC patients including cancer samples and adjacent normal samples were obtained from The Cancer Genome Atlas (TCGA) database. The CpG sites in 20 m 6 A regulators were identified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A recent study further reported a predictive model for OS consisting of age, clinical stage, pathological tissue grade, tumor size, and ethnicity [ 31 ]. A predictive nomogram for endometrial carcinoma combining long noncoding RNA expression profiles and m6A regulator-related CpG sites was also shown recently [ 32 , 33 ]. Here, we constructed a new prognostic nomogram using age, clinical stage, histologic grade, tumor invasion, histological type and S100A2 levels as indicators that can be used by physicians to improve the accuracy of identifying high-risk patients.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study further reported a predictive model for OS consisting of age, clinical stage, pathological tissue grade, tumor size, and ethnicity [ 31 ]. A predictive nomogram for endometrial carcinoma combining long noncoding RNA expression profiles and m6A regulator-related CpG sites was also shown recently [ 32 , 33 ]. Here, we constructed a new prognostic nomogram using age, clinical stage, histologic grade, tumor invasion, histological type and S100A2 levels as indicators that can be used by physicians to improve the accuracy of identifying high-risk patients.…”
Section: Discussionmentioning
confidence: 93%
“…Many facets of RNA metabolism were affected by the m6A alteration, including RNA processing, nuclear export, RNA translation, and decay ( 37 ). According to new findings, m6A methylation played a critical role in endometrial cancer through a variety of pathways and expanded the potential for early cancer detection and therapy ( 38 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that FTO, RBM15, and YTHDF1 are critical in the progression and prognosis of endometrial cancer (82,97). Interestingly, Zhang et al found that CpG sites located at the m 6 A regulatory site may be considered a potential prognostic feature of endometrial cancer patients (98). In a more detailed study, 19 m 6 A RNA methylation regulators were abnormally expressed in endometrial carcinoma.…”
Section: Prognostic Effect Of M 6 a Rna Methylation Regulators On End...mentioning
confidence: 91%